How to create a national spectrum strategy in harmony with EU requirement - Gábor Kolláth; Péter Vári (International Telecommunications Society (ITS), 2011)
The radio spectrum is a scarce resource for many different services (TV and radio broadcasting, navigation, mobile, wireless and satellite communications, radio location) and is used by many other commercial or scientific applications (alarms, remote controls, microphones, medical equipment, etc.). It is also used by public services (defense, security, safety and scientific activities (meteorology, Earth observation, radio astronomy and space research, etc.). Our goal is to use the spectrum the most effective and coherent way in order to stimulate growth, competitiveness and employment. All this can create higher costs, lead to wasted opportunities for business and reduce the take-up of innovative services to the detriment of consumers. Spectrum management has a strong cross-border dimension. The global unified markets are based on radio-communication services like GSM services but we have to avoid harmful interference. A coordinated spectrum policy can create only a genuine single market for radio services and equipment.
Keywords: 330; strategy methodology; spectrum management; country study